Digital Initiatives for Access and Quality in Higher Education: An Overview - Ahmad, Shakeel (Prabandhan: Indian Journal of Management, 2020)
Higher education plays an important role to develop good and creative individuals and is viewed as a powerful means to build a knowledge - based society. It is the foundation for growth in productivity, income, and employment opportunities, which enhance the quality of life. The challenges currently before India’s higher education system are enhancing access and improving quality. Digital transformation has brought rapid changes in the very nature of the higher education landscape. Digital initiatives are very important and a boon for both increasing access and improving quality in higher education. The Government of India has started digital initiatives for higher education. The launch of these digital initiatives has necessitated evolving strategies for effective adoption and utilization in higher educational institutions (HEIs) to achieve the anticipated benefits and outcomes for sustainable change of these digital initiatives. This paper presented an overview on the digital initiatives particularly launched by the government since 2015 to enhance access and promote quality in higher education. Few suggestions for the effective adoption and utilization to achieve the benefits of these digital initiatives in HEIs were also made.